Utilizing Quizizz as Learning Media in Improving Student Reading Skills In Teaching And Learning Process - Ulfaika, Romlah; Hasbiana, Untari; Midina, Shalsa; Wibowo, Amiruddin Hadi (Proceeding of International Joint Conference on UNESA, 2025)
The purpose of this study was to determine the effectiveness of using the quizizz application as a learning media to improve student reading skills. This research used a quasi-experimental method and the population was all the students of class VIII at SMP Negeri 2 Tarakan. The sampling technique was carried out by the purposive sampling with a sample of 64 students. The instrument was prepared by looking at some indicators from syllabus and lesson plan (RPP) for data collection. This research instrument was test sheets which consisted of pretest and posttest. The result of this study showed that there was a significant difference between the experimental group and control group. It was proven by the result of the average score of student. The average result in pretest and posttest in experiment group were 45.63 and 68.28. Meanwhile, the average result in pretest and posttest in control group were 38.75 and 49.38. It showed that there was a significant difference from the use of the Quizizz application as a learning media. The result from the independent sample test showed that the t-test (3,938) was higher than t-table (1,670). In this study, the researcher found that there was a significant difference after using Quizizz as a learning media. Therefore, it can be concluded that the use of Quizizz as a learning media had proven to be effective for improving the student English reading skills in teaching and learning English.